The Sisters brothers [videorecording (DVD)] - Audiard, Jacques; Audiard, Jacques; Reilly, John C., 1965-; Phoenix, Joaquin; Gyllenhaal, Jake, 1980-; deWitt, Patrick, 1975- (Twentieth Century Fox Home Entertainment, 2019)
Follows the notorious hit men duo, the Sisters brothers, as they pursue a gold prospector in the Old West and get caught up in the Gold Rush.